Sistem Pendidikan Indonesia Pada Zaman Orde Lama (Periode 1945-1966) - Zahwa Wulandari; Hayu Ramadhani; Intan Dwi Azzahra; Thalita Miftah (PT. Hasba Edukasi Mandiri, 2026)
This article discusses the Indonesian education system during the Old Order period from 1945 to 1966. The purpose of this writing is to describe the policies, structure, and characteristics of national education in the context of nation-building in the post-independence era. The method used is a literature study by analyzing relevant sources such as books, historical documents, and scientific journals. The findings show that the education system during the Old Order period was characterized by a spirit of nationalism, nation-character building, and efforts to equalize access to education. Education policies were directed toward liberation from the colonial system, the development of a national curriculum, and strengthening the role of education in reinforcing national identity. However, its implementation faced challenges such as limited resources, infrastructure, and an uneven distribution of teaching staff. In conclusion, education during the Old Order period became the initial foundation for the formation of Indonesia’s national education system. Although it was not yet optimal, this period played an important role in establishing the ideological and institutional basis that influenced the development of education in subsequent periods.